MANAGEMENT OF SETT ROT [CERATOCYSTIS PARADOXA (DE SEYNES) MOREAU] IN SUSTAINABLE SUGARCANE INITIATIVE (SSI) NURSERIES - P. S. SHANMUGAM; M. SANGEETHA; N. A. SARAVANAN; N. TAMILSELVAN (The Bioscan, 2015)
Healthy sugarcane seedling production in Sustainable Sugarcane Initiative (SSI) is hindered by the incidence of sett rot Ceratocystis paradoxa(De Seynes) Moreau which causes 90% loss of seedlings. Among the different treatment combinations, bud chip treatment with Pseudomonas fluorescens@ 10 g/l+ Trichoderma viride @ 4 g/l+ mixing of P. fluorescens@ 1kg/250kg of coco peat and bud chip treatment with P. fluorescens@ 10 g/l followed by 0.1% thiophanatemethyltreatment were found to be highly effective with the germination percent- age of 88 and 85 during south west monsoon and 83 and 81 during north east monsoon season respectively.Sett rot incidence in the above treatments was 15.5 and 13% during south west monsoon and 22.5 and 16.00% during north east monsoon respectively. The bud chip treatment with carbendazim and thiophanate methyl recorded 64 and 67% germination during south west and 62 and 61% during north east monsoon seasons. Economic analysis of management modules showed that 1.87 and 1.78 benefit cost ratio for P. fluorescens + T. viride combination and 1.84 and 1.83 benefit cost ratio for P. fluorescens + thiophanatemethyl combination during south west and north east monsoon season respectively.The results revealed that the combination of biocontrol agents can be effectively used for the management of sett rot in sugarcane nurseries.